Soluções auto-similares para a equação quase-geostrofica e comportamento assintotico - Ferreira, Lucas Catão de Freitas, 1977- (2005)
Orientadores : Helena Judith Nussenzveig Lopes, Jose Antonio Carrillo de la Plata